Pengaruh Pembelajaran Tahfidz Qur’an Terhadap Tingkat Kecemasan Siswa - Hadinata, Cristian; Ulum, Bambang Bahrul; Kusuma, Cefi Wijaya; Wahidin, Khaerul; Maulana, Muhammad Azka (Universitas Muhammadiyah Yogyakarta, 2023)
One of the school's efforts in realizing a generation of love for the Qur'an is to create a 30 juz tahfidz program. However, there are previous studies that mention that there is anxiety arising from memorizing the Qur'an and on the other hand there are previous studies that show that memorizing the Qur'an improves mental health. The purpose of this study is to confirm whether there is an influence between the tahfidz program and the emergence of anxiety levels and describe the dynamics of the tahfidz program at ARSI Islamic School Brebes Central Java and its implications for the mental health of its memorizers. This study uses a quantitative approach with simple linear regression techniques with a total of 59 students in the ARSI Islamic School Brebes Central Java boarding school. Where 19 students follow the tahfidz program and 40 students do not follow the tahfidz program. The data collection tool used the HARS questionnaire. The results of this study indicate that the anova value of 0.12 has no significant effect between the tahfidz program and anxiety in students.